Yield performance of resistant derivatives from cross involving DPW 621-50 and HD 2967 cultivars of wheat - Pal Singh, Rupinder; Bains, Navtej Singh; Sohu, Virinder Singh (Journal of Cereal Research, 2016)
In this study, 191 highly stripe rust resistant lines were selected from F6 population of cross DPW 621-50/HD 2967 with the objective of recovering transgressive segregants for yield and related traits. Yield performance of these 191 lines along with checks and parental lines was evaluated across two crop seasons (2013-14 and 2014-15). Preliminary yield trial (2013-14 season) displayed a large amount of variation present in derivatives for different yield related traits. Evaluation yielded 40 highly productive entries out of which, two lines namely, BWL 4438 (PBW 709) and BWL 4443 (PBW 724) were promoted to national co-ordinated trials. Healthy and vigorous ears were observedto produce more number of grains per spike but early flowering genotypes showed lesser number of grains per spike and were poor yielding. During 2014-15 season evaluation of selected forty lines was taken up along with the parents and checks. Entry BWL 4550 was found to have highest 1000-grain weight (51.050 g), surpassing all the checks. An important observation was recorded that grains per spike had negative correlation with plant height thus showing the adverse effect of lodging on grain filling due to excessive plant height. On thewhole, strategy for extracting the transgressive segregants for differentyield related parameters from the derivatives of cross involving twogenetically diverse released cultivars (DPW 621-50 and HD 2967)proved to be an effective strategy.